2019
DOI: 10.1111/nhs.12641
|View full text |Cite
|
Sign up to set email alerts
|

Nursing practice in stroke rehabilitation: Perspectives from multi‐disciplinary healthcare professionals

Abstract: In this qualitative, descriptive study, we explored the status of and factors related to nursing practice for stroke rehabilitation in China, considering the perspectives of multi‐disciplinary healthcare professionals. Fifteen participants were interviewed in depth, followed by field observations at three healthcare institutions. Data were analyzed using ethnographic data analysis methods. Current nursing practice for patients with stroke emerged as a cultural domain that included nine patterns: coordination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
14
0
5
Order By: Relevance
“…Rapid rehabilitation nursing combined with continuous nursing after discharge helps patients to establish a positive attitude, helps patients master home nursing operation, promotes the integration of hospital and family, and makes patients actively cooperate with functional rehabilitation training, thus making patients physically and mentally healthy. e combined application of the two nursing modes has greatly improved patients' anxiety, depression, and other bad emotions caused by diseases, which is helpful to promote CI patients in recovery period to maintain a gradual recovery mentality, give patients great encouragement and support, and then significantly improve their living standards [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid rehabilitation nursing combined with continuous nursing after discharge helps patients to establish a positive attitude, helps patients master home nursing operation, promotes the integration of hospital and family, and makes patients actively cooperate with functional rehabilitation training, thus making patients physically and mentally healthy. e combined application of the two nursing modes has greatly improved patients' anxiety, depression, and other bad emotions caused by diseases, which is helpful to promote CI patients in recovery period to maintain a gradual recovery mentality, give patients great encouragement and support, and then significantly improve their living standards [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that there was a statistically significant difference in nurses' knowledge and practices regarding the neurological evaluation of stroke patients. This could be due to nurses' clinical practices before ischemic stroke nursing management protocol implementation was mainly focused on general nursing care for stroke patients regardless of the disease phase (Meng, Chen, & Zhou, 2020). This finding is consistent with Novak (2019) who mentioned that 73.1% of participant nurses were able to apply NIHSS correctly after implementing an education program on NIHSS among staff nurses working in the neurological ICU.…”
Section: Discussionsupporting
confidence: 76%
“…In order to avoid the use of analgesics, nursing staff should explain how to divert pain attention to patients when the pain can be tolerated. The nursing staff were required to strengthen ward inspection [ 10 ] to inquire about the pain degree every day. If the VAS score exceeds 4 points, then report the pain to the doctor in time.…”
Section: Methodsmentioning
confidence: 99%